Stigmatisation in chronic hepatitis B and C infections-time to debunk the myth! - Qadri, Sabreena; Ashraf, Aadil; Khan, Javid Ahmed; Shah, Altaf; Hussain, Arshad (International Journal of Research in Medical Sciences, 2023)
Background: Hepatitis B and C are chronic diseases with mental and social impacts which can result in poor quality of life. The routes of transmission and lack of education among the masses may cause stigmatisation of the affected patients. The aim of the study was to document the stigmatisation among chronic hepatitis B and C positive patients. Methods: The 242 patients suffering from hepatitis B and C were included in the study. Stigma experienced from relatives, friends, spouse and health care providers was assessed using a semi structured questionnaire. Results: Majority of the patients were males 174 (72%). The 162 (67%) were hepatitis B infected and 76 (32%) were Hepatitis C infected and 4 were dual infected. Male patients were significantly more affected than females in term of changes in lifestyle (86% versus 61%) and changes in relationship with the spouse (89% versus 16%). Significantly more females than males reported feelings of loneliness and isolation (64% versus 30%). Stigma was marked in terms of disease transmission, with 170 (70%) of patients fearing that they could transmit the infection to others. Marital relationships were affected for 52% of married patients. Around 80% unmarried patients were experiencing delay in getting married. Conclusions: Patients comments showed a sense of family and societal discrimination resulting in feelings of disappointment which could be changed by educational interventions, effective patient and family centric awareness and scientific models of approach.